Kesetaraan antara laki-laki dan perempuan dalam pernikahan perspektif hukum Islam - Dyana, Dyana (AS-SAKINAH, 2024)
In Islamic law, kafa`ah is applied as something that is "considered" in marriage, but is not related to its validity. It is with this kafa'ah that Islam places great value on women. Each bride-to-be has the right to choose a person who is equal to her, as well as a man, who has the right to choose a woman who is equal to him to be his wife. Of course it is really one thing that needs to be considered in matters of marriage. For example, like a free person, he has the right to choose a partner who is also free. Except if there is indeed a sense of sincerity to accept a slave as a potential partner who is wanted while he is a free person. The research method used is literature study, which is a research whose preparation is the same as other research but the source and method of data collection by taking data in the library, reading, recording, and processing research materials. Research with literature studies is also a research categorized as a scientific work because data collection is carried out with a strategy in the form of a research methodology. There are several scholarly opinions regarding kafa'ah in a marriage, as explained by Ahmad Royani. According to the majority of scholars, kafa'ah is something that is very important for the continuity and harmony of a marriage, although according to them kafa'ah is not a condition for the validity of a marriage. That is, the concept of kafa'ah is only the virtue and validity of marriage between people who are not sekufu, this opinion is based on the words of the Prophet Muhammad SAW which means "Indeed I will prevent the marriage of national women, unless they marry men who are sekufu".